Determinants of social cohesion: Cross-country evidence - Yabibal Mulualem Walle (German Institute of Development and Sustainability (IDOS), 2022)
Noting that few studies to date have investigated the determinants of social cohesion in a comprehensive and systematic manner, this paper examines the macro-level determinants of social cohesion using a panel of up to 92 developing and developed countries for the period 1990-2020. Employing the system GMM dynamic panel data estimator, which addresses endogeneity concerns by means of internal instruments, I find that the levels of education, government size, globalisation, and economic development have significantly positive effects on most dimensions of a country's social cohesion. In contrast, inflation, corruption and income inequality are detrimental to social cohesion.
Keywords: 330; Social cohesion; education; globalisation; inflation; corruption; government size; income inequality; GDP per capita